2016
DOI: 10.1038/srep36135
|View full text |Cite
|
Sign up to set email alerts
|

Survival of mature T cells depends on signaling through HOIP

Abstract: T cell development in the thymus is controlled by a multistep process. The NF-κB pathway regulates T cell development as well as T cell activation at multiple differentiation stages. The linear ubiquitin chain assembly complex (LUBAC) is composed of Sharpin, HOIL-1L and HOIP, and it is crucial for regulating the NF-κB and cell death pathways. However, little is known about the roles of LUBAC in T-cell development and activation. Here, we show that in T-HOIPΔlinear mice lacking the ubiquitin ligase activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Alternative approaches would be needed to capture changes in subpopulation ubiquitylation. These data could be further expanded through use of reagents to identify linear polyubiquitin chains, which are known to have roles in T cell development and homeostasis [45][46][47] but cannot be detected by di-glycine remnant proteomics.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative approaches would be needed to capture changes in subpopulation ubiquitylation. These data could be further expanded through use of reagents to identify linear polyubiquitin chains, which are known to have roles in T cell development and homeostasis [45][46][47] but cannot be detected by di-glycine remnant proteomics.…”
Section: Discussionmentioning
confidence: 99%
“…We and others showed that LUBAC plays a role in activating the canonical NF-kB pathway and inhibiting TNF-a-induced cell death (12)(13)(14)(15). The role of LUBAC during development and function of B and T lymphocytes has also been dissected (16,(27)(28)(29)(30). In B cells, LUBAC plays crucial roles in TD and TI-II Ab responses by controlling CD40and TACI-mediated activation of the canonical NF-kB and ERK pathways, respectively; it also regulates B1 cell development (16).…”
Section: Discussionmentioning
confidence: 99%
“…At ambient temperatures it orders in inverted cubic spinel ferrite with the tetrahedral (A) site occupied by Fe 3+ ions and with Fe 2+ and Fe 3+ ions coexisting at the same octahedral (B) site 26 . Magnetite undergoes a first-order transition below 120 K where the resistivity increases by two orders of magnitude and the structural distortions from cubic symmetry occur 27,28 . It is suggested that this transition is driven by a charge ordering of Fe 2+ and Fe 3+ ions 29 .…”
Section: Soft Ferrimagnetic Fe3o4mentioning
confidence: 99%